1993
DOI: 10.1111/j.1755-618x.1993.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

National character, regional culture, and the values of Canadians and Americans

Abstract: Cette étude analyse des données ayant fait l'objet de sondages à l'échelle nationale et qui serviront à evaluer la thèse de S.M. Lipset en regard avec certaines divergences caractérisant la population canadienne et américaine. L'étude traitera principalement d'une question, à savoir si les particularités régionales de chacun des deux pays constituent un élément aussi fondamental que leur dissemblance si l'on compare leurs valeurs. Les résultats du sondage indiquent que la barrière entre le Canada et les États‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
0
30
1
Order By: Relevance
“…Research comparing the national characters of the two countries, however, suggested that the "argument for the existence of distinct national characters requires extensive rethinking (Baer, Grabb, & Johnston, 1993, p. 27; see also Baer, Grabb, & Johnston, 1990). Findings by Baer et al (1990Baer et al ( , 1993 showed few important divisions or significant national differences in values based on political boundaries. They noted that these similarities might be explained not only by geographical proximity, but also by (except Quebec) language and exposure to the same (predominantly American) media and popular culture (Baer et al, 1993, p. 29).…”
Section: Discussionmentioning
confidence: 93%
“…Research comparing the national characters of the two countries, however, suggested that the "argument for the existence of distinct national characters requires extensive rethinking (Baer, Grabb, & Johnston, 1993, p. 27; see also Baer, Grabb, & Johnston, 1990). Findings by Baer et al (1990Baer et al ( , 1993 showed few important divisions or significant national differences in values based on political boundaries. They noted that these similarities might be explained not only by geographical proximity, but also by (except Quebec) language and exposure to the same (predominantly American) media and popular culture (Baer et al, 1993, p. 29).…”
Section: Discussionmentioning
confidence: 93%
“…In their analyses of the World Values Surveys (WVS) from the early 1990s, Grabb and Curtis (2005, 227;2002, 46) did find that Southerners were the most trusting or accepting about political institutions among the four regional groups they considered, but Quebecers were not clearly at the opposite extremesee also Baer, Grabb, and Johnston (1993); Kanji and Nevitte (2000). Another study, based on the World Values Surveys from the early 1980s, showed that French Canadians, while comparatively low on general respect for authority, actually expressed somewhat higher levels of confidence than both English Canadians and Americans in certain political institutions, including the civil service and Parliament/Congress (Baer, Curtis, Grabb, and Johnston 1995, 188).…”
Section: Previous Findings Comparing Canada and The United Statesmentioning
confidence: 95%
“…Southern residence is included in the model because previous studies (Keele, 2005) show that Southerners have lower levels of political trust. The primary reason why trust levels are lower is that the political culture in the South is more conservative (Baer, Grabb, & Johnston, 1993). Simpson (2006) argues that the Southern states have higher distrust due to the legacy of the civil war.…”
Section: Notesmentioning
confidence: 99%